A Radiologia dos Tumores Malignos da Nasofaringe (Cavum) - Cabral, João Carlos (2023)
The Author points out that thenasopharingeal tumors were initially reported in 1845, and only understood in 1811 by TROTTER. He also emphasizes: 1) The need for new studies of the complex pathophysiology of these malignancies, not yet well understood. 2) The higher incidence of these tumors in oriental races. 3) The gross and mycroscopic pathology with a list of its most prominent mycroscopic findings. 4) The nasopharingel anatomy, in brief. 5) The value of the radiodiagnostic methods and the minimum number and types of films and techniques in the work-up. 6) The differencial diagnosis, in particular juvenile angio-fibroma. 7) The diagnostic importance, in this tumor of the anterior arching of the maxiliary sinus posterior wall, in the lateral X—rays film.